Deep Learning Implementation to Determine Vehicle Groups at Halim Toll Gate: Deep Learning Implementation to Determine Vehicle Groups at Halim Toll Gate - Yedizha Afif Farhani; Fauziah Fauziah; Nurhayati Nurhayati (Institute of Computer Science (IOCS), 2020)
One of the solutions for the smooth flow of vehicles in big cities is to build toll road infrastructure. The toll road is a freeway with a paid system that can only be passed by four or more wheeled vehicles. There is often a buildup of vehicles when making payment transactions because the vehicle classification system is still manual or a wrong class occurs when payment transactions. To improve service quality, the use of deep learning to determine the class of vehicles or to correct transaction results is deemed effective. CNN method will classify vehicles based on two-dimensional image data. Vehicle data collection is done at the Halim Toll Gate..